Tribological Behavior of Atmospheric Plasma-Spray-Deposited Ni-Based Composite Coatings at Different Speeds and Temperatures - Gautam R.K.S.; Rao U.S.; Mishra S.; Tyagi R. (My University, 2025)
In order to examine the effect of sliding speeds on the elevated temperature tribological performance of atmospheric plasma-sprayed Ni-Al-Ag-MoS2 (NAMB), Ni-Al-Ag-MoS2-5 wt.% hBN (NAMB5) and Ni-Al-Ag-MoS2-10 wt.% hBN (NAMB10) composite coatings, friction and wear tests were conducted against alumina ball as a counter face using ‘a rotary ball on disk configuration’ at a constant load of 5 N and different sliding speeds 0.3, 0.5, 0.7 and 0.9 m/s from room temperature (RT) to 800 °C using a high-temperature tribometer. Both coefficient of friction and wear rate were found to decrease with increasing speed from 0.3 to 0.7 m/s with a marginal increase beyond that for all the coatings. However, coating NAMB5 exhibited better lubricity in comparison with the other coatings at all sliding speeds and temperatures. The coefficient of friction recorded for this coating decreased from 0.51 to 0.23 at a sliding speed of 0.3 m/s and from 0.48 to 0.1 at a sliding speed of 0.7 m/s as the temperature was increased from RT to 800 °C. The results indicate the existence of a synergistic action of hBN in combination with Ag and MoS2 in providing lower friction and wear, thus highlighting the potential of hBN as an effective solid lubricant to stabilize the friction in a wide range of temperatures and speeds. © 2020, ASM International.